Pemberdayaan Peternak Melalui Pemanfaatan Teknologi Inseminasi Buatan Pada Sapi Potong Di Desa Bamba Puang, Kecamatan Anggeraja, Kabupaten Enrekang: Pemanfaatan Teknologi Inseminasi Buatan - Hamka; Yulia Irwina Bonewati; Muhammad Farid (Universitas Mataram, 2024)
This community service activity is expected to increase the knowledge and insight of beef cattle farmers in Bamba Puang Village, Anggeraja District, Enrekang Regency, regarding artificial insemination (AI) technology. Through a series of education, farmers are given an understanding of the importance of choosing good feed, how to detect estrus in acceptors, and proper maintenance management to support the success of AI. This activity was carried out on December 13, 2024, attended by local farmers and organized by Thematic KKN students of Muhammadiyah Bone University. The results of this activity show that farmers increasingly understand important aspects in the implementation of AI, which is expected to increase the productivity of beef cattle. In addition, this activity is also expected to reduce negative issues circulating regarding AI, and encourage farmers to be more confident in adopting this technology. It is hoped that with further training from the government, farmers can be more experienced and successful in their livestock business.